JSP and XML : integrating XML and web services in your JSP application - Kochmer, Casey (Addison-Wesley, 2002)
JavaServer Pages technology allows Web developers and designers to rapidly develop and easily maintain information-rich, dynamic Web pages that are platform independent. JavaServer Pages technology uses XML-like tags and "scriptlets" written in the Java programming language to encapsulate the logic that generates the content for the page. This book is geared towards JavaServer Pages developers, bringing them a confident functionality and usage with XML. There are many examples within the book that are usable in other projects. The reader learns to build and expand custom JSP tags, which can realistically be used on any JSP project. Many advanced topics are also covered to maintain the interest of the more accomplished JSP developer.